(untitled) (Eurasian Research Bulletin, 2023)
This scientific article presents scientific information about epidemiology, i.e., infectious diseases. An epidemic is a widespread spread of infectious diseases in a country, region, or country. In this case, the number of patients will be 510 times more than usual